2023
DOI: 10.1038/s43705-023-00253-5
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal changes soil bacterial interactions with fungal wood decomposition

Abstract: Although microbes are the major agent of wood decomposition - a key component of the carbon cycle - the degree to which microbial community dynamics affect this process is unclear. One key knowledge gap is the extent to which stochastic variation in community assembly, e.g. due to historical contingency, can substantively affect decomposition rates. To close this knowledge gap, we manipulated the pool of microbes dispersing into laboratory microcosms using rainwater sampled across a transition zone between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Heat tree analysis indicated that N input increases the abundance of Proteobacteria , Firmicutes , and Bacteroidetes and slightly increases the abundance of Acidobacteria and Verrucomicrobia (at medium and high N levels). Fungi are considered to have more oligotrophic characteristics than bacteria (Wang & Kuzyakov, 2024), often are less sensitive, and have inconsistent responses to long‐term nutrient addition (de Vries et al., 2018; Jansson & Hofmockel, 2022). The relative abundances of hemicellulose, cellulose, and chitin degradation genes were observed under N input in the long term (Figure 5), suggesting that N decreased the production of C‐degrading enzymes by soil bacteria and further suppressed SOM mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat tree analysis indicated that N input increases the abundance of Proteobacteria , Firmicutes , and Bacteroidetes and slightly increases the abundance of Acidobacteria and Verrucomicrobia (at medium and high N levels). Fungi are considered to have more oligotrophic characteristics than bacteria (Wang & Kuzyakov, 2024), often are less sensitive, and have inconsistent responses to long‐term nutrient addition (de Vries et al., 2018; Jansson & Hofmockel, 2022). The relative abundances of hemicellulose, cellulose, and chitin degradation genes were observed under N input in the long term (Figure 5), suggesting that N decreased the production of C‐degrading enzymes by soil bacteria and further suppressed SOM mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…N input shifts microbial communities by giving an advantage to copiotrophs over oligotrophs, which utilize labile and stable compounds, respectively (Dai et al., 2018; Ramirez et al., 2012). Bacteria and fungi degrade labile and stable substances by producing hydrolytic and oxidative enzymes (Cusack et al., 2011; Jian et al., 2016), whereas bacteria are more efficient in the utilization of labile, and fungi for persistent compounds (Wang & Kuzyakov, 2024). N input can decrease microbial N mining from SOM and increase microbial C use efficiency, without affecting total microbial biomass (Spohn et al., 2016; Zang, Blagodatskaya, Wang, et al., 2017).…”
Section: Introductionmentioning
confidence: 99%